Pengaruh Perhatian Orangtua terhadap Hasil Belajar Siswa Bidang Studi PAI di SMP Negeri 01 Koto Besar Kabupaten Dharmasraya - Yuanda, Rival; Afrinaldi, Afrinaldi; Arifmiboy, Arifmiboy; Husni, Arman (Lembaga Yasin AlSys, 2023)
The background of this research is that there are parents who have various kinds of busyness, one of which is work which causes a student to pay less attention to how learning problems are experienced by children at school. and there are also parents who are reluctant to attend school invitations because the student's behavior causes students to lack interest in learning so that the learning outcomes they get are not good. This study aims to determine the effect of parental attention on student learning outcomes at SMPN 01 Koto Besar.This research belongs to the correlative quantitative research, namely to see the effect of two different variables. The population in this study were class VIII students, totaling 104 students. The research sample was 27 students who were taken using the Total Sampling technique. Data was collected using a Likert scale instrument and then processed using the Statistical Product and Service Solution (SPSS) Version 20 hypothesis test.Based on the results of the correlation analysis, it is known that if the pcount value is greater than the ptable, it can be said to be correlated. In this study the ptable was 0.381, the pcount value in this study was 0.371 greater than the ptable 0.381, so it can be said that parental attention and learning outcomes are correlated. The variable size of parents' attention to the learning outcome variable is calculated by D = r2 × 100%, a D of 32% is obtained. So it can be concluded that the influence of parental attention on student learning outcomes in SMP 1 Negeri Koto Besar is 32%, it can be said that Ha is accepted and H0 is rejected and there is a significant relationship between parental attention to student learning outcomes in SMP 1 Negeri Koto Big.